Bovine immune response to leptospira antigen in different novel adjuvants and vaccine delivery platforms. Issue 18 (16th April 2020) - Wilson-Welder, Jennifer H.; Boggiatto, Paola; Nally, Jarlath E.; Wafa, Emad I.; Alt, David P.; Hornsby, Richard L.; Frank, Ami; Jones, Douglas E.; Olsen, Steven C.; Bowden, Ned B.; Salem, Aliasger K.
Highlights: Leptospira vaccines for cattle can be improved by the use of novel adjuvants. Efficacious cattle vaccines induce humoral and cellular immunity, including IL-17A. Two different polymer formulations enhanced responses to leptospira antigen in cattle. Oil-based adjuvant enhanced magnitude of Th1 type immunity to leptospira antigen. Abstract: Leptospirosis is a global zoonosis causing significant economic losses for cattle production. Current cattle vaccines against leptospirosis need improvement to provide efficacy against multiple serovars, reduce shedding in urine, and to induce earlier and more robust immune responses. In this study, Leptospira borgpetersenii serovar Hardjo strain 203 antigen was combined with novel adjuvants (a biodegradable polyanhydride compressed rod implant (VPEAR), poly(diaminosulfide) microparticles, a water-oil-water emulsion adjuvant, and aluminum hydroxide) to develop novel vaccines. Cattle were immunized twice, at a 4 week interval, with inoculums containing adjuvants alone or leptospira antigens and immune responses were compared to responses of cattle receiving a commercial monovalent leptospirosis vaccine (Spirovac). All animals were inoculated with a single dose of Spirovac at 20 weeks to assess antigen recall responses. Serum antibody responses were increased (P > 0.05) at 8 and 20 weeks after vaccination in cattle receiving inoculums containing leptospira antigens combined with water-oil-emulsion, poly(diaminosulfide) microparticles (PNSN-MP), or aluminum hydroxide and in cattle vaccinated with Spirovac. Humoral responses were predominantly IgG1 isotypes. Antigen-specific proliferative responses were detected after initial vaccination in cattle vaccinated with Spirovac, PNSN-MP and water-oil-water treatments. Most proliferative responses occurring within CD4+ and gamma delta T cell populations expressing CD45RO and CD25 markers, a response consistent with an effector memory phenotype. Antigen-specific immune responses were not detected in cattle vaccinated with VPEAR after initial inoculation, but were detected in the antigen recall responses. PBMCs from cattle vaccinated with Spirovac, oil-water-oil, or PNSN-MP treatments had increased (P < 0.05) IL-17A release after in vitro stimulation with leptospirosis antigens, whereas all groups produced IFN-γ and IL-17A after in vitro stimulation during the antigen recall response. Our data demonstrates that combining leptospirosis antigens with these adjuvants enhances immunogenicity in cattle. Interpretative Summary: Vaccination of livestock is a key mechanism for minimizing transmission of leptospirosis, a zoonotic disease. Leptospirosis vaccines for cattle need to be improved to provide greater levels of protection from kidney colonization, better immune responses, and protection against multiple serovars. This could be accomplished using new vaccine adjuvants. In this study, several novel adjuvants were evaluated for their ability to induce effective immune responses in cattle to leptospira antigens as compared to currently available vaccines. Data suggested that vaccines containing biodegradable polymer microparticles and oil-emulsion adjuvants induced similar or greater immune responses as compared to a commercial vaccine. Our data suggest these new vaccine formulations warrant further investigation as new vaccine formulations for cattle and other livestock.